Ambiente urbano, qualidade de vida e (in)sustentabilidade em cidades locais : Nossa Senhora da Glória/SE - Jesus, Tânia Santos de (2006)
Being a built-up environment, the city involves the flow of immobilized capital in the space through physical equipments which are used in the production and consumption such as streets, buildings and sewer system. In the city, the natural environment can be transformed into residential, leisure, industrial and commercial areas. The appearance and/or expansion of cities without adequate planning, mainly relating to infrastructure can reflect in future problems that may interfere both in the quality of life of the inhabitants and in the environment quality. Due to the intense changes provoked by human action, the urban ecosystem has shown more and more distinct characteristics and working from the natural systems.The search for a new development standard in order to guarantee natural capital for future generations has brought to discussion the theme of sustainability. In this sense, the urban sustainability has been one of the biggest challenges of present time because of several environmental problems in the cities. This research is based on the rationale that the basic conditions in the city of Nossa Senhora da Glória/SE do not reveal a sustainable development and that public policies can lead to a perspective of reaching urban sustainability. The objective of this work is to analyse the different aspects of the development in Nossa Senhora da Glória/SE urban area, based on socioenvironmental indicators in attempt of identifying which factors can be interfering in the city sustainable development, as well as point to the main measures to be adopted in the field of public policies aiming at urban sustainability. The indicators considered were: solid wastes, basic sanitation, infrastructure, collective well-being, housing, public health, public education, work and income. It was adopted a methodology based on the concept of sustainability, using the following tools: bibliographical revision; fieldwork with photographic registers; interviews with the local inhabitants, and with public agencies and entities; application of questionnaires with the inhabitants; statistical treatment, analysis and discussion of the data collected. The intention of this work is to contribute to the adoption of a new attitude by local population and its governments relating to development. The use of socioenvironmental indicators constitutes a methodological approach that provides the comprehension of urban space processes. In this work, the use of this tool made possible the verification that socioespacial segregation analysed together with environment degradation specially in the outskirts, contributes to its weak degree of sustainability, influencing the inhabitants quality of life.